2008
DOI: 10.1007/s00330-008-0952-7
|View full text |Cite
|
Sign up to set email alerts
|

CT assessment of herniation pits: prevalence, characteristics, and potential association with morphological predictors of femoroacetabular impingement

Abstract: The purpose of this study was to evaluate whether there is a correlation between the presence of herniation pits (HPs) and morphological indicators of cam and pincer femoroacetabular impingement (FAI) based on computed tomography (CT) examinations. CT studies of the pelvis obtained from 200 patients were retrospectively analysed for the presence of HPs and morphological abnormalities of the femoral head and acetabulum. As an indicator for cam FAI, we used the angle alpha, describing the anterior femoral head-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
5
36
4
2
Order By: Relevance
“…Additionally, characteristic femoral chondral fibrocystic changes, today called impingement cysts [11], previously named herniation pits, are localized at the head-neck junction distal to the physis and frequently visible radiographically [11,12,15,18]. Histologically these lesions consist of proliferative fibroblasts forming either dense fibrous tissue or gelatinous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, characteristic femoral chondral fibrocystic changes, today called impingement cysts [11], previously named herniation pits, are localized at the head-neck junction distal to the physis and frequently visible radiographically [11,12,15,18]. Histologically these lesions consist of proliferative fibroblasts forming either dense fibrous tissue or gelatinous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteers were included if they were asymptomatic (no symptoms, no medical history in regard to abnormalities of the hip joint, negative impingement test, and internal hip rotation of greater than 25° at clinical examination by the same author who performed the assessment mentioned above) and were the osseous deformities at the femoral head-neck junction, but there has been some controversy about its accuracy for clinical use, because the validation of the alpha angle measurement revealed only moderate agreement after repeated measurements by the same reader and substantial interobserver differences (12,13). Moreover, researchers in several studies have shown that a substantial portion of the healthy young adult population exhibits some degree of cam-type deformities (14)(15)(16)(17).…”
Section: Musculoskeletal Imaging: Alpha Angle In Femoroacetabular Impmentioning
confidence: 99%
“…In this study, excessive acetabular coverage is defined as a lateral edge angle of .398 as suggested previously (14). This is at odds with a more recent study suggesting a cut-off of .448 (23).…”
Section: Discussionmentioning
confidence: 96%